Menghadirkan Generasi Syakir Untuk Membangun Semangat Patriotisme Di Era Milenial - Hamdi, Saibatul; Musthofa, Khabib (MADINAH, 2019)
The phenomenon of the fading of the millennial generation's sense of pride is actually caused by various factors. Among these factors are the influence of globalization and the increasing trend of youth. This sad fact has actually lowered the spirit of nationalism and national patriotism. Therefore, mental syakir needs to be presented in the middle of this problem. This study aims to review: (1) The younger generation from the perspective of the Qur’an. (2) Uncover millennial generation 3G habits. (3) Presenting the syakir generation in the millennial era. The method used is library research by elaborating the verses of the Qur’an and then linking them with relevant references. The results of this study indicate that: (1) The figure of the younger generation in the Qur’an is Ashabul Kahfi who always maintains his religion even though his environmental conditions are bad at that time. So this attitude must also be owned by the millennial generation. (2) The 3G habits of the millennial generation actually have an impact on the waning of love for their own country. (3) The Qur'anic guidelines in presenting the syakir generation to arouse the spirit of patriotism today, namely by presenting qana'ah in attitudes, developing qalbiah intelligence, and knitting religious nationalism values. Thus this syakir mentality will be attached to the personality of the millennial generation.